Effect of the Pt Precursor and Loading on the Structural Parameters and Catalytic Properties of Pt/Al2O3. Issue 13 (6th June 2019) - Borges, Lais R.; Lopez‐Castillo, Alejandro; Meira, Debora M.; Gallo, Jean Marcel R.; Zanchet, Daniela; Bueno, José Maria C.
Abstract: The effects of promoters and additives on the electronic properties and structural properties of Pt catalysts still need to be understood. The present work investigates the effects of the Pt loading and the use of chloride additive on the structural properties of Pt/Al2 O3 and its catalytic activity towards the WGS reaction. The presence of Cl affected the morphology and oxygen coverage of the Pt nanoparticles. However, these parameters did not affect the surface electronic properties, due to a compensation effect between the size of the Pt 0 core and oxygen coordinated on the shell (NPt‐O ). Despite the structural differences, the catalytic activity for the WGS reaction was similar for the chloride‐free sample and the catalyst containing chloride. The effect of the Pt loading was also studied, with the "apparent" catalytic activity per site of Pt (TOF) decreasing with increasing metal loading. Increasing the Pt loading led to an increase of the low‐coordination Pt 0 sites at the surface of the NPs, resulting in stronger Pt‐CO integration and consequent poisoning of the active sites. Abstract : So strong yet so good : The presence of Cl affected the morphology and oxygen coverage of Pt nanoparticles, but did not affect the surface electronic properties, due to a compensation effect between the size of the Pt 0 core and oxygen coordinated on the shell (NPt‐O ). The Pt loading affected the "apparent" catalytic activity per site of Pt (TOF), due to increase of the low‐coordination Pt 0 sites at the surfaces of the NPs, leading to poisoning of the active sites.